Konsep Kesantunan Berbahasa Dalam Islam - Rusydi Room (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
This article discusses about the character building in utizing language according to Islam. The language sometimes becomes source of conflict because it is social image. Therefore, to minimize root of the conflicts, the cross-culture dialogue should be conducted in order that people can understand one another. Ideally, character building starts from institutions of education, including household, schools, universities, ect. where teachers and lecturers appreciate all languages which students speak, while they teach and train them with a good attitude and good character. A using of language will be effective when users of the language use it in communication activity with wisdom, while wisdom itself can be available as long as they understand the culture and appreciate Islamic values.